PEMBERDAYAAN MASYARAKAT DESA KALISARI DALAM ASPEK EKONOMI, KESEHATAN, LINGKUNGAN, DAN PENDIDIKAN (HIMESBANG CARE 2023) - Nuron Fatah Hidayat; Putra Fajar; Citra Rahmasari; Adistianti Adistianti; Lilis Siti Badriah (Sinergi Abdimas Jurnal Pengabdian Masyarakat, 2024)
Kalisari Village is known as the largest tofu industry center village in Banyumas Regency. Based on the results of observations and interviews, there are several problems related to economic aspects in the tofu industry and MSMEs, health aspects, environmental aspects and educational aspects. The first is the economic problem in terms of marketing products which are still local so that businesses are difficult to develop, the second is the problem of high rates of dengue fever, the third is the problem of environmental pollution resulting from tofu waste, the fourth is the problem of the lack of opportunities for children to develop their interests and talents. In determining various service programs to provide solution assistance, students emphasize socialization and training methods. The solutions implemented include digital marketing outreach and training, free health check facilities, processing tofu waste into fertilizer, and facilitating media opportunities to increase children's creativity. To ensure the sustainability of the benefits from the various activities that have been carried out, cooperation and collaboration between various stakeholders is needed in providing continuous assistance and monitoring. Keywords: Community Empowerment, Tofu Industry, MSMEs, Socialization and Training, Digital Marketing